A case report of ultrasound-guided erector spinae plane nerve block for pediatric renal colic in an emergency department - Mark Noble; Monica Mitta; Jondavid Landon; Donald Byars (Pediatric Emergency Medicine Journal)
Erector spinae plane nerve block (ESPB) has become a frequently used tool of analgesia among anesthesiologists or emergency physicians. The ESPB utilizes a guidance of point-of-care ultrasound and has a favorable safety profile. It had historically been used primarily in operative settings, but has become increasingly used for refractory pain in emergency settings. Here, we present a case of an adolescent with refractory renal colic pain who received an ESPB, performed by an emergency physician, with an improvement in the pain. To our knowledge, this is the first case report of ESPB use for renal colic in a pediatric patient.